Useless old circuit board resources recovery processing system - ZHOU XUEZHI; XIE QINGDONG (2017)
The utility model relates to an useless old circuit board resources recovery processing system, including raw material conveyor, cleaning machine, rubbing crusher, fine crushing machine, inclined plate settler, drying chamber, high voltage static separator and recovery jar, be provided with a plurality of washing liquid shower heads in the cleaning machine, rubbing crusher includes two kinds of rubbing crusher of coarse cracking and grinding, is the fine crushing machine 2 3 level fine crushing machine, the drying chamber includes drying chamber, temperature controller and exhaust apparatus, the utility model discloses constituting simple structure, using the flexibility convenient, throughput is high, and recovery efficiency is high, and no secondary pollution reduces running cost and daily maintaining management cost. 本实用新型涉及种废旧电路板资源回收处理系统，包括原料输送机、清洗机、粉碎机、细破机、斜板沉降器、干燥室、高压静电分离器和回收罐，所述清洗机内设置有若干清洗液喷淋头，所述粉碎机包括粗粉碎和细粉碎两种粉碎机，所述细破机为2-3级细破机，所述干燥室包括干燥腔室、温度控制器和排气装置，本实用新型构成结构简单，使用灵活性方便，处理能力高，回收效率高，无二次污染，降低运行成本和日常维护管理成本